Socio-Hydrology: The New Paradigm in Resilient Water Management - Younos, Tamim; Parece, Tammy; Lee, Juneseok; Giovannettone, Jason; Armel, Alaina J. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
During the third decade of the 21st century, human societies across the world are facing significant water-related problems, such as ecosystem degradation, groundwater depletion, natural and anthropogenic droughts and floods, water-borne health issues, and deforestation. These problems are exacerbated by climate change, a phenomenon that has been accelerated due to human intervention in natural systems since the industrial revolution. There is an urgent need to better understand the interaction of hydrological systems in terms of climate variability and the anthropogenic factors that contribute to the dynamics and resilience of coupled human-water systems and effective risk management in the area of water resource management. Socio-hydrology is an interdisciplinary field that integrates natural and social sciences and aims to study the long-term dynamics of bidirectional feedback in coupled human-water systems. This book on socio-hydrology aims to compile cross-disciplinary scientific endeavors and innovations in research on the development, education, and application of coupled human-water systems. The articles published in this book represent diverse and broad aspects of water management in the context of socio-hydrology systems around the globe. The articles and ideas presented in this book represent a significant source of references for interdisciplinary water science programs and provide an excellent guide for experts involved in the future planning and management of water resources. This book is dedicated to friends of the Green Water-Infrastructure Academy and those who pursue cross-disciplinary water research, education, and management.